Pengaruh Model Pembelajaran Kooperatif Tipe Tgt Berbantuan Media Educaplay Terhadap Hasil Belajar Ipas Kelas V SDN 060970 Bagan Deli - Patresia Situmorang; Robenhart Tamba; Wildansyah Lubis; Imelda Free Unita Manurung; Yusra Nasution (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This research aims to investigate the effect of cooperative learning model Team Games Tournament (TGT) with Educaplay media on science learning outcomes of fifth-grade students at SDN 060970 Bagan Deli. The study employed a quantitative method with a Quasi-Experimental design using pretest and posttest with non-equivalent control-group design. The research subjects were 56 fifth-grade students at SDN 060970 Bagan Deli, selected through purposive sampling technique. Based on the research results, the data analysis showed a significance value (2-tailed) of 0.000 < 0.05. The hypothesis was accepted based on the t-test where t-hitung = 4.524 > t-tabel = 1.673, resulting in the rejection of H0 and acceptance of Ha. The mean score in the control class was 70.53, while the experimental class achieved a mean score of 80.36. The effect size calculation using Cohen's d formula yielded a value of 1.206, which is interpreted as a large effect size. Therefore, it can be concluded that the cooperative learning model TGT with Educaplay media has a significant effect on improving the learning outcomes of fifth-grade students at SDN 060970 Bagan Deli.